Toward accounting for ecoclimate teleconnections: intra- and inter-continental consequences of altered energy balance after vegetation change - Stark, Scott C.; Breshears, David D.; Garcia, Elizabeth S.; Law, Darin J.; Minor, David M.; Saleska, Scott Reid; Swann, Abigail S.; Villegas, Juan Camilo; Aragao, L. E.O.C.; Bella, Elizabeth M.; Borma, Laura de Simone; Cobb, Neil S.; et al. (Landscape Ecology, 2016)
Context: Vegetation is projected to continue to undergo major structural changes in coming decades due to land conversion and climate change, including widespread forest die-offs. These vegetation changes are important not only for their local or regional climatic effects, but also because they can affect climate and subsequently vegetation in other regions or continents through “ecoclimate teleconnections”. Objectives: We propose that ecoclimate teleconnections are a fundamental link among regions within and across continents, and are central to advancing large-scale macrosystems ecology. Methods and results: We illustrate potential ecoclimate teleconnections in a bounding simulation that assumes complete tree cover loss in western North America due to tree die-off, and which predicts subsequent drying and reduced net primary productivity in other areas of North America, the Amazon and elsewhere. Central to accurately modeling such ecoclimate teleconnections is characterizing how vegetation change alters albedo and other components of the land-surface energy balance and then scales up to impact the climate system. We introduce a framework for rapid field-based characterization of vegetation structure and energy balance to help address this challenge. Conclusions: Ecoclimate teleconnections are likely a fundamental aspect of macrosystems ecology needed to account for alterations to large-scale atmospheric-ecological couplings in response to vegetation change, including deforestation, afforestation and die-off. © 2015, Springer Science+Business Media Dordrecht.